1996
DOI: 10.2337/diab.45.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cilazapril and Amlodipine on Kidney Function in Hypertensive NIDDM Patients

Abstract: Contrasting information has been reported concerning the course of renal function in NIDDM with hypertension alone or in association with renal damage. The aim of the present study was to elucidate the course of the glomerular filtration rate (GFR) in hypertensive NIDDM patients during antihypertensive therapy. Furthermore, we compared the effects of ACE inhibitors (cilazapril, Inibace, Roche, Milan, Italy) and Ca(2+)-channel blockers (amlodipine, Norvasc, Pfizer, Rome, Italy). Of the hypertensive NIDDM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…Although the FACET and ABCD trials showed the beneficial cardiovascular effects of ACEIs over dhCCBs, other studies, such as HOT and Syst-Eur [64], showed the substantial safety and efficacy of CCBs in preventing cardiovascular end points in type 2 diabetes. With respect to renal effects, studies by Velussi et al [36] and Fogari et al [25], as well as analysis of renal end points in the ABCD trial [48], showed similar effects of ACEIs and dhCCBs on the course of nephropathy, except for effects on proteinuria. Whether the weaker antiproteinuric effect of dhCCB translates into a worse nephroprotective outcome after a longer follow-up remains to be established.…”
Section: Antihypertensive Treatment Strategies In Patients With Type mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the FACET and ABCD trials showed the beneficial cardiovascular effects of ACEIs over dhCCBs, other studies, such as HOT and Syst-Eur [64], showed the substantial safety and efficacy of CCBs in preventing cardiovascular end points in type 2 diabetes. With respect to renal effects, studies by Velussi et al [36] and Fogari et al [25], as well as analysis of renal end points in the ABCD trial [48], showed similar effects of ACEIs and dhCCBs on the course of nephropathy, except for effects on proteinuria. Whether the weaker antiproteinuric effect of dhCCB translates into a worse nephroprotective outcome after a longer follow-up remains to be established.…”
Section: Antihypertensive Treatment Strategies In Patients With Type mentioning
confidence: 99%
“…Despite optimism about the use of ACEIs raised by placebocontrolled studies by Ravid et al [29], showing renoprotective effects of 7 years of treatment with enalapril in normotensive MA patients, and some other studies (follow-up ≥ 12 months) suggesting that ACEIs could be superior to other regimens in hypertensive patients in various stages of renal involvement [30][31][32][33][34][35], other studies reported similar nephroprotection after ACEIs, to that after nifedipine in normotensive [17], or to that of amlodipine [36], nitrendipine [37], or atenolol [38] in hypertensive patients. In type 2 diabetes, much new information has been recently communicated.…”
Section: Treatment Of Hypertension In Type 2 Diabetic Patients With Nmentioning
confidence: 99%
“…Some studies have reported a similar renoprotective capacity of CCBs and ACE inhibitors in diabetic nephropathy [13][14][15]. The results of long-term studies are, nevertheless, required to prove whether or not both classes of drugs can be used as first-step therapy in diabetic nephropathy.…”
Section: Calcium Channel Blockers and Renal Functionmentioning
confidence: 99%
“…The good effect of the dihydropyridine could, in this case, be mostly ascribed to a significantly better BP control when nitrendipine, alone or in combination, was administered. The recent presentation of data from the AASK study [17], in which amlodipine in combination with non-ACE inhibitor therapy was significantly worse than an ACE inhibitor-based combination therapy (Data presented at the American Society of Nephrology meeting, Toronto, October [11][12][13][14][15][16]2000 ) in blacks with renal disease of various origins, does not seem to confirm the equality among ACE inhibitors and CCBs. This year data from the IDNT study [18] will be presented, and data comparing amlodipine and irbesartan (in combination in most cases) in type 2 diabetic nephropathy will be revealed and contribute to clarify this issue.…”
Section: Calcium Channel Blockers and Renal Functionmentioning
confidence: 99%
“…Although some small studies have found that CCBs and ACE inhibitors are equally renoprotective [37,38], others have shown an increase in proteinuria and worsening renal function in patients treated with CCBs [39,40].…”
Section: Role Of Calcium Channel Blockers In the Progression Of Kidnementioning
confidence: 99%